A method for preparing high temperature resistant composite lining

By using a sandwich structure in the PTFE lining, the problem of PTFE lining is easily expanded and tear at high temperatures in the prior art, the high-strength peeling force and good high-temperature stability of the composite lining are achieved, which extends the service life and simplifies the construction process.

CN115593073BActive Publication Date: 2025-03-25JIANGSU JINYOU NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211109801.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-13
Publication Date
2025-03-25
Estimated Expiration
2042-09-13

AI Technical Summary

Technical Problem

The existing PTFE lining preparation methods have many production processes, difficulty in preparing large diameter or special-shaped linings, and easy expansion and tearing at high temperatures.

Method used

The composite lining plate preparation method adopts a sandwich structure, and bonds the PTFE molded plate with glass fiber woven fabric through a fusible fluoroplastic film to form a composite lining plate with high strength peeling force and good high temperature stability.

Benefits of technology

It realizes the high-strength peeling force and good high-temperature stability of the composite lining, extends the service life, and simplifies the on-site construction process, and can adapt to large-size equipment and special-shaped structural parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003843505180000061
    Figure BDA0003843505180000061
  • Figure BDA0003843505180000071
    Figure BDA0003843505180000071
  • Figure BDA0003843505180000081
    Figure BDA0003843505180000081
Patent Text Reader

Abstract

The present application relates to the technical field of composite linings, and in particular to a method for preparing a high temperature resistant composite lining, which comprises the following steps: raw material pretreatment and heating and compounding. The present application has the advantages of being able to simultaneously meet the requirements that the prepared lining has good high temperature stability, simple on-site construction, and can be made into large diameter linings and special-shaped linings as required.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite linings, and in particular to a method for preparing a high temperature resistant composite lining. Background Art

[0002] Polytetrafluoroethylene (PTFE) is a high molecular polymer made by polymerizing tetrafluoroethylene as a monomer. It has a very low friction coefficient and good heat resistance, cold resistance, acid resistance and alkali resistance. In addition to being able to react with molten alkali metals, it is not corroded by any substance. Even if it is boiled in hydrofluoric acid, aqua regia, oleum, or sodium hydroxide, it will not change at all. At the same time, PTFE is resistant to various organic solvents and is almost insoluble in all solvents. Therefore, many equipment or pipelines with strong acid or strong alkali media currently choose PTFE as a lining material to protect the equipment or pipeline body.

[0003] At present, there are three main methods for preparing PTFE for equipment lining: winding tube loose lining method, extrusion tube tight lining method, and powder pressing method.

[0004] However, the winding tube loose lining method has more production processes and is more troublesome to construct on site. The diameter of the lining produced by the extrusion tube tight lining method is affected by the processing equipment and is often only capable of processing straight pipes with a diameter of less than 300 mm. The powder pressing method produces the lining by one-time integral molding, and the quality of the lining is greatly affected by the raw materials and process. Therefore, all three methods have certain limitations, including difficulties in on-site construction, difficulty in preparing large-diameter or special-shaped linings, and the PTFE lining plate being easily expanded and torn at high temperatures. Summary of the invention

[0005] In order to simultaneously meet the requirements of simple on-site construction, good high-temperature stability of the manufactured lining, and the ability to produce large-diameter linings and special-shaped linings, the present application provides a method for preparing a high-temperature resistant composite lining.

[0006] The present application provides a method for preparing a high temperature resistant composite lining plate using the following technical scheme:

[0007] A method for preparing a high temperature resistant composite lining comprises the following steps:

[0008] S1. Raw material pretreatment:

[0009] The fusible fluoroplastic film is subjected to corona treatment to obtain the fluoroplastic film to be composited;

[0010] Adding a silane coupling agent to a fluororesin emulsion to obtain a mixed solution, wherein the fluororesin emulsion is an emulsion corresponding to the fusible fluoroplastic film raw material, coating the mixed solution on the outer surface of a glass fiber woven fabric, drying and sintering the glass fiber woven fabric to obtain a glass fiber woven fabric to be composited;

[0011] The outer surface of the PTFE molded plate is activated and coated with the mixed solution, followed by drying and sintering to obtain a PTFE molded plate to be composited;

[0012] S2, heating and laminating: preheating the PTFE molded plate to be laminated and the glass fiber woven fabric to be laminated, placing the fluoroplastic film to be laminated between the polyethylene molded plate to be laminated and the glass fiber woven fabric to be laminated, heating to melt the fluoroplastic film to be laminated, cooling to obtain a composite plate.

[0013] By adopting the above-mentioned technical scheme, the present application forms a sandwich structure by bonding the PTFE molded plate and the glass fiber woven cloth through a fusible fluoroplastic film, so that the prepared composite lining has high-strength peeling force. It is expected that at an operating temperature of less than 250°C, the probability of problems such as tearing, bulging and delamination during long-term use is low; at the same time, the unique sandwich structure makes the composite lining prepared by the present application have good high-temperature stability, so that the service life of the composite lining prepared by the application is much higher than the common PTFE lining on the market; and the composite lining prepared by the present application can be cut and spliced ​​according to the conditions of the on-site equipment and pipelines to adapt to large-size equipment and special-shaped structural parts. The cut and spliced ​​composite lining can be glued and fixed to the inner surface of the equipment with high-temperature glue, and on-site construction is simple and easy.

[0014] Preferably, the activation treatment method is one of sodium naphthalene treatment or plasma treatment.

[0015] By adopting the above technical scheme, sodium naphthalene treatment is to remove part of the fluorine element by reacting the sodium naphthalene treatment liquid with PTFE, introduce polar groups such as hydroxyl, carbonyl and unsaturated bonds, so that the surface energy of the PTFE molded plate is increased, the contact angle is reduced, the wettability is improved, and it changes from difficult to stick to sticky, laying a foundation for the subsequent compounding with glass fiber woven fabric through fusible fluoroplastic film; plasma treatment is a process of replacing the polymer functional groups on the surface of the PTFE molded plate with different atoms using ions in the plasma to increase the surface energy of the PTFE molded plate, and also makes the PTFE molded plate change from difficult to stick to sticky.

[0016] Preferably, during the sodium naphthalene treatment, the concentration of the sodium naphthalene treatment solution is 0.3-0.5 mol / L.

[0017] By adopting the above technical scheme, the sodium naphthalene treatment liquid will react with the CC bond and CF bond of PTFE, but mainly destroys the CF bond and removes fluorine atoms; as the concentration of the sodium naphthalene treatment liquid increases, the etching effect on the surface of the PTFE molded plate becomes more and more intense, and the degree of removal of fluorine elements on the surface of the molded plate by the sodium naphthalene treatment liquid becomes higher and higher, but at this time, the degree of damage to the CC bond is also increasing, affecting the strength of the PTFE molded plate. The present application controls the concentration of the sodium naphthalene treatment liquid to ensure the defluorination effect to ensure the bonding effect while ensuring the compressive strength of the final composite lining.

[0018] Preferably, during plasma treatment, the plasma inert gas is H2 / N2.

[0019] By adopting the above technical solution, H2 treatment is used to improve the efficiency of plasma activation treatment, reduce the time required for plasma treatment, and effectively reduce production costs. At the same time, N2 with stable properties is doped to ensure the stability and safety of the discharge process.

[0020] Preferably, the thickness of the PTFE molded plate is 0.1-3 mm.

[0021] By adopting the above technical scheme, the PTFE molded plate has good high temperature resistance, acid and alkali corrosion resistance, and no gas-liquid penetration, and the performance of the PTFE molded plate improves with the increase of the thickness of the molded plate. When the thickness of the PTFE molded plate is too small, the high temperature stability of the obtained composite lining is insufficient; when the thickness of the PTFE molded plate reaches a certain degree, the obtained composite lining already has good high temperature stability; because in the hot pressing composite process, it is necessary to control the upper limit of the temperature of the upper and lower heating rollers to protect the PTFE molded plate and the glass fiber woven fabric, and continue to increase the thickness of the PTFE molded plate, the excessively thick PTFE molded plate limits the heat transfer, and the fusible fluoroplastic film as the middle layer may not be fully melted, resulting in the obtained composite lining not being bonded tightly enough, and the heat resistance, aging resistance, etc. are all reduced; the present application controls the production cost while ensuring the high temperature stability of the obtained composite lining by controlling the thickness of the PTFE film pressing plate.

[0022] Preferably, the thickness of the fusible fluoroplastic film is 0.1-0.8 mm.

[0023] Preferably, the thickness of the fusible fluoroplastic film is 0.2-0.5 mm.

[0024] By adopting the above technical scheme, the fusible fluoroplastic film melts at high temperature and plays the role of bonding the PTFE molded plate and the glass fiber woven cloth. When the thickness of the fusible fluoroplastic film is too small, the bonding effect is poor and a stable sandwich structure cannot be formed well, resulting in the composite lining plate may have bulging, delamination and other problems during use, which also affects the high temperature stability of the composite lining plate and limits the service life of the composite lining plate. However, when the fusible fluoroplastic film is too thick, the various properties of the prepared composite lining plate are reduced. This may be because, in order to make the fusible fluoroplastic film fully melt, the heating time becomes longer, causing the fusible fluoroplastic film to partially decompose, thereby affecting the performance of the prepared composite lining plate.

[0025] Preferably, the melt index of the fusible fluoroplastic film is 6-12 g / (10 min).

[0026] By adopting the above technical scheme, the higher the melt index, the better the fluidity of the fluoroplastic film. During the heating and compounding process, the fluoroplastic film melts and flows around, fully filling the gap between the PTFE molded plate and the glass fiber woven cloth, so that the PTFE molded plate and the glass fiber woven cloth are tightly bonded, thereby obtaining a composite lining plate with high-strength peeling force and good high-temperature stability; however, with the increase of the melt index, the toughness and aging resistance stability of the fusible fluoroplastic film continue to decrease, which increases the possibility of brittle fracture of the obtained composite lining plate, and also limits the high temperature resistance of the composite lining plate; the present application ensures that the composite lining plate has good compressive strength and high temperature resistance by selecting a fusible fluoroplastic film with a suitable melt index.

[0027] Preferably, the glass fiber woven fabric has a thickness of 0.1-1 mm.

[0028] By adopting the above technical scheme, the glass fiber woven fabric has the advantages of small thermal deformation, high compressive strength, good high temperature resistance, etc. The lower limit of the thickness of the glass fiber woven fabric is controlled, so that the preparation process is relatively stable, and the probability of the thin glass fiber woven fabric being damaged due to heat is reduced; as the thickness of the glass fiber woven fabric increases, the heat resistance of the prepared composite lining plate continues to increase; in order to obtain a composite lining plate with good heat resistance, it is necessary to ensure that the fusible fluoroplastic film located in the middle layer is fully melted during the preparation process. When the thickness of the glass fiber woven fabric is too thick, when limiting the temperature of the upper and lower heating rollers to reduce the possibility of damage to the PTFE mold plate and the glass fiber woven fabric during the hot pressing composite process, the fusible fluoroplastic film may not be fully melted, resulting in the prepared composite lining plate not being bonded tightly enough, so that the heat resistance, aging resistance and other properties of the composite lining plate are reduced.

[0029] Preferably, the glass fiber woven fabric is selected from glass fiber woven fabric whose surface does not contain lubricating substances such as paraffin or has been dewaxed.

[0030] By adopting the above technical scheme, the performance of the composite lining is guaranteed by selecting glass fiber woven fabrics whose surface does not contain lubricating substances such as paraffin or has been dewaxed. This is because paraffin has a lubricating effect. After the wax-containing glass fiber woven fabric is melted, the presence of paraffin reduces the friction between the glass fiber woven fabric and the PTFE molded plate, thereby reducing the stability of the bonding between the glass fiber woven fabric and the PTFE molded plate, and increasing the possibility of delamination or bulging of the composite lining during operation.

[0031] In summary, the present application includes at least one of the following beneficial technical effects:

[0032] 1. The present application has produced a composite liner with a sandwich structure. The sandwich structure enables the composite liner to have high-strength peeling force and good high-temperature stability. The service life of the composite liner is much longer than that of the common PTFE liner on the market. At an operating temperature of less than 250°C, it is expected that the composite liner will have a low probability of tearing, bulging, and delamination after long-term use. At the same time, the composite liner can be cut and spliced ​​according to the conditions of the on-site equipment and pipelines to adapt to large-size equipment and special-shaped structural parts. The cut and spliced ​​composite liner can be fixed to the inner surface of the equipment with high-temperature glue, and the on-site construction is simple and easy.

[0033] 2. The present application ensures the degree of removal of fluorine atoms by controlling the concentration of the sodium naphthalene treatment solution, introduces more polar groups, and increases the surface energy of the PTFE molded plate, reduces the contact angle, improves the wettability, and changes from difficult to stick to sticky. At the same time, by controlling the concentration of the sodium naphthalene treatment solution, the degree of damage to the CC bond is limited, thereby ensuring the compressive strength of the final composite lining. DETAILED DESCRIPTION

[0034] The present application is further described in detail below with reference to the embodiments.

[0035] raw material

[0036] PFA film: PFA is a copolymer of a small amount of perfluoropropyl perfluorovinyl ether and polytetrafluoroethylene; the melt index is 9g / (10min), and the thicknesses are 0.05mm, 0.1mm, 0.2mm, 0.3mm, 0.5mm, 0.8mm, and 1mm, respectively; the thickness is 0.3mm, and the melt indexes are 4g / (10min), 6g / (10min), 12g / (10min), and 14g / (10min), respectively.

[0037] FEP film: FEP is a fluorinated ethylene propylene copolymer; the thickness is 0.3 mm and the melt index is 9 g / (10 min).

[0038] ETFE film: ETFE is an ethylene-tetrafluoroethylene copolymer; the thickness is 0.3 mm and the melt index is 9 g / (10 min).

[0039] Silane coupling agent: Model KH-560, effective substance content ≥99%.

[0040] PFA emulsion: active substance content ≥50%, product number is D450.

[0041] FEP emulsion: active substance content ≥50%, item number 121D.

[0042] ETFE emulsion: active substance content ≥50%, item number is 1908632.

[0043] Wax-free glass fiber woven fabric: Made of glass fiber with a diameter of 2-10μm, with thicknesses of 0.05mm, 0.1mm, 0.5mm, 1mm, and 1.5mm respectively.

[0044] Waxed glass fiber woven fabric: Made of glass fiber with a diameter of 2-10μm and a thickness of 0.5mm.

[0045] PTFE molded sheet: non-porous molded sheet with thicknesses of 0.05mm, 0.1mm, 1mm, 2mm, 3mm, and 3.5mm.

[0046] Sodium naphthalene treatment liquid: Model is HJ-001, the concentration can be adjusted according to actual needs.

[0047] PFA mixed solution, FEP mixed solution, ETFE mixed solution: add silane coupling agent to PFA emulsion to obtain PFA fusion solution, and the silane coupling agent accounts for 0.2-2wt% of the PFA mixed solution according to the mass fraction. Similarly, keep the proportion of silane coupling agent and the preparation steps of the mixed solution unchanged, replace PFA emulsion with FEP emulsion or ETFE emulsion, and you can get FEP mixed solution and ETFE mixed solution accordingly.

[0048] Commercially available PTFE liner: density is 2.12-2.24g / cm 3 The operating temperature is 20-250℃, the friction coefficient is 0.01, and the impact strength is 0.6-6.4MPa.

[0049] Example

[0050] Example 1

[0051] A method for preparing a high temperature resistant composite lining comprises the following steps:

[0052] S1. Raw material pretreatment:

[0053] Take a PTFE molded plate with a thickness of 1 mm, a PFA film with a thickness of 0.3 mm and a melt index of 9 g / (10 min), and a wax-free glass fiber woven fabric with a thickness of 0.5 mm;

[0054] Performing corona treatment on both sides of the PFA film to obtain a fluoroplastic film to be composited;

[0055] A layer of PFA mixed solution is coated on one side of the wax-free glass fiber woven fabric to obtain the glass fiber woven fabric to be sintered;

[0056] One side of the PTFE molded plate is subjected to a sodium naphthalene activation treatment, wherein the concentration of the sodium naphthalene treatment solution is 0.4 mol / L; a layer of PFA mixed solution is coated on the activated side to obtain a PTFE molded plate to be sintered;

[0057] The PTFE molded plate to be sintered and the glass fiber woven fabric to be sintered are placed in an oven respectively, first heated to 80-95°C, maintained for 15 minutes, then heated to 250-315°C, maintained for 15 minutes, and finally heated to 360-400°C, maintained for 15 minutes, and naturally cooled to room temperature to obtain the PTFE molded plate to be composited and the glass fiber woven fabric to be composited.

[0058] S2, heating compound:

[0059] The PTFE molded plate to be composited and the glass fiber woven fabric to be composited are placed in an oven and preheated to more than 250°C;

[0060] The oven heating roller is divided into two rollers, the upper and lower rollers are electromagnetic heating rollers, the upper roller is in direct contact with the PTFE molded plate to be composited, the surface temperature of the upper roller is between 280-325℃, the lower roller is in direct contact with the glass fiber woven fabric to be composited, the surface temperature of the lower roller is controlled at 300-380℃, the pressure between the upper and lower rollers is between 0.01-0.5MPa, and the outer periphery of the two heating rollers is provided with an insulation box to reduce heat loss;

[0061] The fusible fluoroplastic film is placed between the heated PTFE molded plate to be composited and the glass fiber woven fabric to be composited, and the three are put into a high-temperature hot press for hot pressing and composite. The linear speed of the pressing roller is 0.65m / min, and the heating roller is an electromagnetic heating roller. During the hot pressing process, the surface temperature of the PTFE plate is controlled to be ≤325℃, and the surface temperature of the fusible fluoroplastic film is ≥310℃; after the hot pressing and composite is completed, it is naturally cooled to room temperature and taken out to obtain a composite lining.

[0062] S3. Machining: trim the composite lining and cut it into composite panels of specified length and width.

[0063] Embodiment 2, 3

[0064] In Examples 2 and 3, the types of fusible fluoroplastic film and fluororesin emulsion are adjusted on the basis of the preparation method of Example 1. In Example 2, the fusible fluoroplastic film is selected from FEP film and the fluororesin emulsion is selected from FEP emulsion; in Example 3, the fusible fluoroplastic film is selected from ETFE film and the fluororesin emulsion is selected from ETFE emulsion.

[0065] Comparative Example

[0066] Comparative Example 1

[0067] Comparative Example 1 uses a commercially available PTFE liner.

[0068] Performance testing

[0069] 1. Compressive strength test: At a temperature of 25°C, use a compression tester to test the compressive strength.

[0070] 2. Aging resistance test: Place the product to be tested in a double 85 test box. After running it in a high temperature (85°C) and high humidity (85% RH) environment for 1000 hours, observe whether cracks appear on the surface of the product.

[0071] 3. High temperature stability test: maintain 30% humidity, limit the temperature to 250°C, keep the temperature constant for 0.5h, then cool naturally to room temperature, cycle 100 times, and check whether bulging occurs.

[0072] Examples 1-3 and Comparative Example 1 were subjected to compressive strength tests and aging resistance tests, and Examples 1-3 were additionally subjected to high temperature stability tests. The test results are shown in Table 1.

[0073] Table 1 Performance test data of Examples 1-3 and Comparative Example 1

[0074]

[0075] Referring to Table 1, the compressive strength, aging resistance and high temperature stability of Examples 1-3 are better than those of Comparative Example 1. This may be because the PTFE molded plate has good high temperature resistance, acid and alkali corrosion resistance, and no gas and liquid penetration. The glass fiber woven fabric has the advantages of small thermal deformation, high compressive strength, and good high temperature resistance. The PFA film, FEP film and ETFE film all have excellent chemical resistance and heat resistance. After the three are bonded to form a composite liner with a sandwich structure, the composite liner combines the advantages of the three. The fluororesin plastic film is used as an intermediate layer, which melts at high temperature and is tightly bonded to the PTFE molded plate and the glass fiber woven fabric respectively, so that the prepared composite liner has a high-strength peeling force. It can be inferred that the composite liner is very stable in normal working conditions. In addition, since the high temperature resistance of the glass fiber woven fabric is better than that of the PTFE molded plate, the fluororesin plastic film as the intermediate layer also plays a role in protecting the PTFE molded plate. Combined with the above reasons, the service life of the composite liner is much higher than that of the common PTFE liner on the market.

[0076] Compared with the single-layer comparative example 1, the presence of the sandwich structure greatly enhances the compressive strength of the prepared composite lining. This may be because after high-temperature hot-pressing compounding, the fluororesin plastic film with good adhesion serves as the middle layer, which promotes the close bonding between the PTFE molded plate and the glass fiber woven fabric. After the three are combined, a better compressive strength is achieved than the three alone.

[0077] Moreover, compared with Comparative Example 1, after the composite lining is machined in Examples 1-3, it can be cut and spliced ​​according to actual needs to produce a large-diameter lining or a special-shaped lining, which greatly improves the adaptability of the composite lining and broadens the application range of the composite lining.

[0078] In order to further study the influence of various components and preparation parameters on the high temperature resistant composite lining, the present application further carries out the following examples for verification.

[0079] Embodiment 4-7

[0080] On the basis of the preparation method of Example 1, the concentration of the sodium naphthalene treatment solution when the PTFE molded plate is treated with sodium naphthalene in S1 is adjusted. In Example 4, the concentration of the sodium naphthalene treatment solution is 0.2 mol / L; in Example 5, the concentration of the sodium naphthalene treatment solution is 0.3 mol / L; in Example 6, the concentration of the sodium naphthalene treatment solution is 0.5 mol / L; in Example 7, the concentration of the sodium naphthalene treatment solution is 0.6 mol / L.

[0081] Example 1 and Examples 4-7 were subjected to the above compressive strength test, aging resistance test, and high temperature stability test. The test results are shown in Table 2.

[0082] Table 2 Performance test data of Example 1 and Examples 4-7

[0083]

[0084] Referring to Table 2, Comparative Example 1 and Examples 4-7, as the concentration of the sodium naphthalene solution increases, the compressive strength and high temperature stability of the obtained composite liner continue to rise. This may be because the sodium naphthalene treatment solution reacts with the CF bond of PTFE, destroys the CF bond and removes fluorine atoms, introduces polar groups such as hydroxyl, carbonyl and unsaturated bonds, increases the surface energy of the PTFE molded plate, reduces the contact angle, improves wettability, and changes from difficult to stick to sticky. As the concentration of the sodium naphthalene treatment solution increases, the etching effect on the surface of the PTFE molded plate becomes more and more intense, and the sodium naphthalene treatment solution removes more and more fluorine elements on the surface of the molded plate, making PTFE more and more easily bonded, so that the obtained composite liner structure is more stable and the performance is more excellent.

[0085] However, when the concentration of the sodium naphthalene treatment solution is too high, the compressive strength is reduced. This may be because PTFE also contains a large number of CC bonds. Although the sodium naphthalene treatment solution mainly reacts with CF bonds, it also reacts with CC bonds. As the concentration of the sodium naphthalene treatment solution increases, the degree of damage to the CC bonds continues to increase. When the concentration of the sodium naphthalene treatment solution is too high, the compressive strength of the composite lining is affected. Therefore, the present application controls the concentration of the sodium naphthalene treatment solution within the range of 0.3mol / L-0.5mol / L, while ensuring the defluorination effect to ensure the bonding effect, the compressive strength of the final composite lining is guaranteed.

[0086] Examples 8-10

[0087] In Example 8-10, based on the raw material ratio of Example 1, the method of activating the PTFE molded plate in S1 is adjusted to plasma treatment. In Example 8, the gas during the plasma treatment is H2 / N2; in Example 9, the gas during the plasma treatment is H2; in Example 10, the gas during the plasma treatment is H2 / Ar.

[0088] Example 1 and Examples 8-10 were subjected to the above compressive strength test, aging resistance test, and high temperature stability test. The test results are shown in Table 3.

[0089] Table 3 Performance test data of Example 1 and Examples 8-10

[0090]

[0091] Referring to Table 3, comparing Example 1 with Examples 8-10, there is little difference in performance between Example 1 and Example 8. This is because plasma treatment is a process in which the polymer functional groups on the surface of the PTFE molded plate are replaced with different atoms using ions in the plasma to increase the surface energy of the PTFE molded plate, and also makes the PTFE molded plate change from difficult to bond to bondable.

[0092] The various properties of Example 8 are greater than those of Example 9. This may be because, in Example 9, pure H2 is too active and the discharge process is not stable enough, resulting in uneven surface activation of the PTFE molded plate, which results in insufficient bonding of PTFE during hot pressing.

[0093] The performance of Example 8 is similar to that of Example 10, because the argon gas in Example 10 is also very stable. However, the cost of argon gas is relatively high. In the present embodiment, the gas used in the plasma treatment is set to H2 / N2, thereby controlling the production cost while ensuring the effect and efficiency of the plasma treatment.

[0094] Examples 11-15

[0095] Examples 11-15 are based on the preparation method of Example 1, and PTFE molded plates of different thicknesses are selected in S1. In Example 11, the thickness of the PTFE molded plate is 0.05 mm; in Example 12, the thickness of the PTFE molded plate is 0.1 mm; in Example 13, the thickness of the PTFE molded plate is 2 mm; in Example 14, the thickness of the PTFE molded plate is 3 mm; in Example 15, the thickness of the PTFE molded plate is 4 mm.

[0096] Example 1 and Examples 11-15 were subjected to the above compressive strength test, aging resistance test, and high temperature stability test. The test results are shown in Table 4.

[0097] Table 4 Performance test data of Example 1 and Examples 11-15

[0098]

[0099] Referring to Table 4, comparing Example 1 with Examples 11-14, when the thickness of the PTFE molded plate is too small, the high-temperature stability of the obtained composite lining is insufficient, and various properties of the PTFE molded plate are improved with the increase of the thickness of the PTFE molded plate.

[0100] Comparing Example 14 and Example 15, when the thickness of the PTFE molded plate reaches a certain level, the prepared composite lining plate already has good high-temperature stability. Since in the hot pressing composite process, it is necessary to control the upper limit of the temperature of the upper and lower heating rollers to protect the PTFE molded plate and the glass fiber woven fabric, if the thickness of the PTFE molded plate is continuously increased, the excessively thick PTFE molded plate will limit the heat transfer, and the fusible fluoroplastic film as the middle layer may not be fully melted, resulting in the prepared composite lining plate not being bonded tightly enough, and the heat resistance and aging resistance are reduced.

[0101] The present application controls the thickness of the PTFE membrane pressing plate, thereby controlling the production cost while ensuring the high temperature stability of the prepared composite lining plate.

[0102] Examples 16-21

[0103] In Examples 16-21, based on the preparation method of Example 14, different thickness FEP films were selected while ensuring that the melt index of the FEP film in S1 remained unchanged. In Example 16, the thickness of the FEP film was 0.05 mm; in Example 17, the thickness of the FEP film was 0.1 mm; in Example 18, the thickness of the FEP film was 0.2 mm; in Example 19, the thickness of the FEP film was 0.5 mm; in Example 20, the thickness of the FEP film was 0.8 mm; and in Example 21, the thickness of the FEP film was 1 mm.

[0104] Example 14 and Examples 16-21 were subjected to the above compressive strength test, aging resistance test, and high temperature stability test. The test results are shown in Table 5.

[0105] Table 5 Performance test data of Example 14 and Examples 16-21

[0106]

[0107] As shown in Table 5, the FEP film melts at high temperature and plays a role in bonding the PTFE molded plate and the glass fiber woven fabric. Comparing Example 14 with Examples 16-21, as the thickness of the FEP film increases, the various properties of PTFE are continuously improved. This may be because when the thickness of the FEP film increases, the bonding effect becomes better and better, and the sandwich structure formed becomes more and more compact and stable.

[0108] However, when the FEP film is too thick, the properties of the composite liner obtained are reduced. This may be because, in order to fully melt the FEP, the heating time becomes longer, resulting in partial decomposition of the FEP, thus affecting the performance of the composite liner obtained.

[0109] Examples 22-25

[0110] In Examples 22-25, based on the preparation method of Example 14, FEP films with different melt indexes were selected while ensuring that the thickness of the FEP film in S1 remained unchanged. In Example 22, the melt index of the FEP film was 4 g / (10 min); in Example 23, the melt index of the FEP film was 6 g / (10 min); in Example 24, the melt index of the FEP film was 12 g / (10 min); and in Example 25, the melt index of the FEP film was 14 g / (10 min).

[0111] Example 14 and Examples 22-25 were subjected to the above compressive strength test, aging resistance test, and high temperature stability test. The test results are shown in Table 6.

[0112] Table 6 Performance test data of Example 14 and Examples 22-25

[0113]

[0114]

[0115] Referring to Table 6, comparing Example 14 with Examples 22-25, as the melt index increases, the various properties of the composite lining board obtained continue to increase. This is because the higher the melt index, the better the fluidity of the fluoroplastic film. During the heating and compounding process, the fluoroplastic film melts and flows everywhere, fully filling the gap between the PTFE molded plate and the glass fiber woven fabric, so that the PTFE molded plate and the glass fiber woven fabric are tightly bonded; at the same time, as the melt index increases, the toughness and aging resistance stability of the FEP film continue to decrease, affecting the high temperature resistance of the composite lining board, and increasing the possibility of brittle fracture of the composite lining board. Therefore, when the melt index is too high, the various properties of the composite lining board decrease instead. Therefore, the present application ensures the performance of the composite lining board obtained by selecting a FEP film with a suitable melt index.

[0116] Examples 27-30

[0117] In Examples 27-30, based on the preparation method of Example 14, wax-free glass fiber woven fabrics of different thicknesses are selected in S1. In Example 27, the thickness of the glass fiber woven fabric is 0.05 mm; in Example 28, the thickness of the glass fiber woven fabric is 0.1 mm; in Example 29, the thickness of the glass fiber woven fabric is 1 mm; and in Example 30, the thickness of the glass fiber woven fabric is 1.5 mm.

[0118] Example 14 and Examples 27-31 were subjected to the above compressive strength test, aging resistance test, and high temperature stability test. The test results are shown in Table 7.

[0119] Table 7 Performance test data of Example 14 and Examples 27-31

[0120]

[0121] Referring to Table 7, comparing Example 14 with Examples 27-29, the various properties of Example 27 are relatively poor, which may be because the glass fiber woven fabric has the advantages of small thermal deformation, high compressive strength, good high temperature resistance, etc. When the thickness of the glass fiber woven fabric is too small, the temperature of the lower heating roller is controlled to ensure that the fusible fluoroplastic film is fully melted, and the too thin glass fiber woven fabric is prone to partial melting due to uneven heating; as the thickness of the glass fiber woven fabric increases, the heat resistance of the obtained composite lining plate continues to increase.

[0122] Comparing Example 29 and Example 30, in order to obtain a composite lining with good heat resistance, it is necessary to ensure that the fusible fluoroplastic film located in the middle layer during the preparation process is fully melted. When the thickness of the glass fiber woven fabric is too thick, when limiting the temperature of the upper and lower heating rollers to reduce the possibility of damage to the PTFE molded plate and the glass fiber woven fabric during the hot pressing composite process, the fusible fluoroplastic film may not be fully melted, resulting in the composite lining being not tightly bonded, causing the various performances of the composite lining to deteriorate.

[0123] Embodiment 31

[0124] In Example 31, based on Example 14, the type of glass fiber woven fabric selected in S1 is adjusted, and waxed glass fiber woven fabric is selected. The thickness of the waxed glass fiber woven fabric is the same as the thickness of the wax-free glass fiber woven fabric in Example 14, both of which are 0.5 mm.

[0125] Example 14 and Example 31 were subjected to the above compressive strength test, aging resistance test, and high temperature stability test. The test results are shown in Table 8.

[0126] Table 8 Performance test data table of Example 14 and Example 31

[0127]

[0128] As shown in Table 8, all properties of Example 14 are better than those of Example 31. This may be because paraffin wax has a lubricating effect. After the wax-containing glass fiber woven fabric is melted, the presence of paraffin wax reduces the friction between the glass fiber woven fabric and the PTFE molded plate, thereby reducing the stability of the combination of the glass fiber woven fabric and the PTFE molded plate, making the sandwich structure of the prepared composite lining plate unstable.

[0129] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a high temperature resistant composite lining, characterized in that: The following steps are involved: Raw material pretreatment: The fusible fluoroplastic film is subjected to corona treatment to obtain the fluoroplastic film to be composited; Adding a silane coupling agent to a fluororesin emulsion to obtain a mixed solution, wherein the fluororesin emulsion is an emulsion corresponding to the fusible fluoroplastic film raw material, coating the mixed solution on the outer surface of a glass fiber woven fabric, drying and sintering the glass fiber woven fabric to obtain a glass fiber woven fabric to be composited; The outer surface of the PTFE molded plate is activated and coated with the mixed solution, followed by drying and sintering to obtain a PTFE molded plate to be composited; Heating and compounding: preheating the PTFE molded plate to be compounded and the glass fiber woven fabric to be compounded, placing the fluoroplastic film to be compounded between the PTFE molded plate to be compounded and the glass fiber woven fabric to be compounded, heating so that the fluoroplastic film to be compounded is completely melted, and cooling to obtain a composite lining plate; Wherein, the activation treatment method is one of sodium naphthalene treatment or plasma treatment. In the case of sodium naphthalene treatment, the concentration of the sodium naphthalene treatment solution is 0.3-0.5 mol / L; in the case of plasma treatment, the plasma inert gas is H2 / N2; The melt index of the fusible fluoroplastic film is 6-12 g / (10 min); The glass fiber woven fabric is selected from glass fiber woven fabric whose surface has been dewaxed.

2. The method for preparing a high temperature resistant composite lining according to claim 1, characterized in that: The thickness of the PTFE molded plate is 0.1-3 mm.

3. The method for preparing a high temperature resistant composite lining according to claim 1, characterized in that: The thickness of the fusible fluoroplastic film is 0.1-0.8 mm.

4. The method for preparing a high temperature resistant composite lining according to claim 3, characterized in that: The thickness of the fusible fluoroplastic film is 0.2-0.5 mm.

5. A method for preparing a high temperature resistant composite lining according to any one of claims 1 to 4, characterized in that: The thickness of the glass fiber woven fabric is 0.1-1 mm.

Citation Information

Patent Citations

  • Fluoroplastic compound product and its making method

    CN101007453A

  • Fluoroplastic composite product and manufacturing method thereof

    EP1946921A1